Infrared-assisted extraction followed by high performance liquid chromatography to determine angoroside C, cinnamic acid, and harpagoside content in Scrophularia ningpoensis - Lina Su; Yinghui Deng; Nianzu Chen; Xiuwen Zhang; Taomin Huang (BMC, 2019)
Abstract Background Angoroside C, cinnamic acid, and harpagoside are bioactive constituents in Scrophularia ningpoensis. Currently, an infrared-assisted extraction (IRAE) method coupled with high-performance liquid chromatography with ultraviolet detection (HPLC-UV) for the analysis of bioactive constituents in this plant is lacking. Methods A method based on HPLC following IRAE has been developed for quantifying angoroside C, cinnamic acid, and harpagoside in Scrophularia ningpoensis. Four main factors, namely, extraction solvent, solid/liquid ratio, illumination time, and distance between the infrared lamp and the round-bottom flask, were optimized for extraction. Furthermore, conventional ultrasonic extraction (USE) and microwave-assisted extraction (MAE) were also investigated to validate the developed method. Results The optimal extraction conditions were as follows: ethanol concentration, 37.5%; solid/liquid ratio, 1:25; illumination time, 10 min; and distance between infrared lamp and round-bottom flask, 3 cm. The results of method validation demonstrated that the developed method meets the requirement of analysis. Conclusion The results show that the IRAE-HPLC is a simple, accurate, and green analytical preparatory method for the potential extraction and quantification of angoroside C, cinnamic acid, and harpagoside in Scrophularia ningpoensis.